1989
DOI: 10.1111/j.1651-2227.1989.tb10904.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Enlargement, Hypertrichosis and Blunted Growth Hormone Secretion in Primary Hypothyroidism

Abstract: Pituitary hyperplasia, hypertrichosis and blunted growth hormone (GH) secretion were observed in three children with untreated primary hypothyroidism. These abnormalities disappeared and improved after thyroid hormone therapy. The recognition of these associations may eliminate unnecessary surgery and GH therapy and lead to the choice of thyroid hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…Severe primary hypothyroidism in children is associated with attenuated spontaneous GH secretion (Buchanan et al 1988, Chernausek & Turner 1989, Nishi et al 1989. In line with these observations are the findings of in vitro studies in cell lines derived from human GH-secreting pituitary tumours, which revealed that thyroid hormones promote GH mRNA accumulation (Chomczynski et al 1993) and GH release (Lamberts et al 1984).…”
Section: Introductionsupporting
confidence: 72%
“…Severe primary hypothyroidism in children is associated with attenuated spontaneous GH secretion (Buchanan et al 1988, Chernausek & Turner 1989, Nishi et al 1989. In line with these observations are the findings of in vitro studies in cell lines derived from human GH-secreting pituitary tumours, which revealed that thyroid hormones promote GH mRNA accumulation (Chomczynski et al 1993) and GH release (Lamberts et al 1984).…”
Section: Introductionsupporting
confidence: 72%
“…Although, hypothyroidism is usually associated with loss of hair, our case showed dark and thick hair on his back which also reported in other cases with untreated primary hypothyroidism [19]. The fact that the hypertrichosis resolved after thyroxine replacement therapy establishes the causal relationship between hypertrichosis and hypothyroidism.…”
Section: Discussionsupporting
confidence: 80%
“…Very few cases of hypertrichosis associated with congenital hypothyroidism have been described. [35] The causal association between hypothyroidism and hypertrichosis has not been reported in neonatal period, although congenitally hypothyroid infants often have a low hairline. Perloff reported four cases of hirsutism in children, who responded to thyroxine replacement therapy.…”
mentioning
confidence: 99%
“…reported three children with untreated primary hypothyroidism resulting in pituitary hyperplasia and hypertrichosis. [5] These abnormalities disappeared after thyroid hormone therapy. In our patient, stimulation of the growth of hair via adrenal androgens by TSH may be the probable pathophysiological mechanism.…”
mentioning
confidence: 99%